Proteomic analysis of the kissing bug Rhodnius prolixus antenna. (July 2017) - Oliveira, Daniele S.; Brito, Nathalia F.; Nogueira, Fabio C.S.; Moreira, Monica F.; Leal, Walter S.; Soares, Marcia R.; Melo, Ana C.A.
Graphical abstract: Highlights: A total of 581 proteins were identified by LTQ Velos Orbitrap mass spectrometry. 17 OBP/PBPs, 6 CSPs, 2 ORs, 3 TRPs and 1 gustatory receptor were identified. 5 OBPs, 1 CSP and olfactory receptors showed phosphorylation site residues. There was a high level of sexual dimorphism in the number of total proteins. Abstract: Reception of odorants is essential in insects' life since the chemical signals in the environment (=semiochemicals) convey information about availability of hosts for a blood meal, mates for reproduction, sites for oviposition and other relevant information for fitness in the environment. Once they reach the antennae, these semiochemicals bind to odorant-binding proteins and are transported through the sensillar lymph until reach the odorant receptors. Such perireceptor events, particularly the interactions with transport proteins, are the liaison between the external environment and the entire neuroethological system and, therefore, a potential target to disrupt insect chemical communication. In this study, a proteomic profile of female and male antennae of Rhodnius prolixus, a vector of Chagas disease, was obtained in an attempt to unravel the entire repertoire of olfactory proteins involved in perireceptor events. Using shotgun proteomics and two-dimensional gel electrophoresis approaches followed by nano liquid chromatography coupled with tandem LTQ Velos Orbitrap mass spectrometry, we have identified 581 unique proteins. Putative olfactory proteins, including 17 odorant binding proteins, 6 chemosensory proteins, 2 odorant receptors, 3 transient receptor channels and 1 gustatory receptor were identified. Proteins involved in general cellular functions such as generation of precursor metabolites, energy generation and catabolism were expressed at high levels. Additionally, proteins that take part in signal transduction, ion binding, and stress response, kinase and oxidoreductase activity were frequent in antennae from both sexes. This proteome strategy unraveled for the first time the complex nature of perireceptor and other olfactory events that occur in R. prolixus antennae, including evidence for phosphorylation of odorant-binding and chemosensory proteins. These findings not only increase our understanding of the olfactory process in triatomine species, but also identify potential molecular targets to be explored for population control of such insect vectors.